2019
DOI: 10.3389/fphys.2019.01303
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Confer Protection by Priming the Immune System of Red Palm Weevil Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae)

Abstract: The immune system of animals, including insects, is the vital factor to maintain the symbiotic interactions between animals and their associated microbes. However, the effects of gut microbiota on insect immunity remain mostly elusive. Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier, is a destructive pest of palm trees worldwide, which has forged alliances with its gut microbiota. Here, we found that the aposymbiotic insects succumbed at a significantly faster rate than conventionally reared (CR) ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 54 publications
(71 reference statements)
4
75
0
Order By: Relevance
“…It suggests that different microbial species may have a different regulatory function in the host. Similar to the above results, the gut commensal microbiota of Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier can help to protect against pathogenic infection by priming the immune system [ 44 ], and the colonization of gut commensal microbiota could enhance the immunocompetence of the host. Futo et al (2016) reported that Tribolium castaneum larvae with less microbiota load showed a decrease in survival rate upon immune challenge by Bt [ 45 ], which indicates that gut microbiota is essential for immune priming.…”
Section: The Interaction Between Host Immunity and Gut Microbiotamentioning
confidence: 66%
“…It suggests that different microbial species may have a different regulatory function in the host. Similar to the above results, the gut commensal microbiota of Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier can help to protect against pathogenic infection by priming the immune system [ 44 ], and the colonization of gut commensal microbiota could enhance the immunocompetence of the host. Futo et al (2016) reported that Tribolium castaneum larvae with less microbiota load showed a decrease in survival rate upon immune challenge by Bt [ 45 ], which indicates that gut microbiota is essential for immune priming.…”
Section: The Interaction Between Host Immunity and Gut Microbiotamentioning
confidence: 66%
“…Although multiple researches have been done to find new ways to control R. ferrugineus , including chemical agents ( Pugliese et al, 2017 ; Wakil et al, 2018 ), biological agents ( Zulkifli, Zakeri & Azmi, 2018 ), and intestinal microbes ( Habineza et al., 2019 ; Muhammad et al, 2019 ), the results are not effective. There are few studies on the molecular characteristics of R. ferrugineus , including transcriptome, genome structure and proteome ( Muhammad et al, 2019 ). Transcriptomics provides complementary data and gene expression data for available genomes for organisms at specific conditions or at different stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…This feeding behavior renders detection of the pest difficult until it is already too late, and most traditional methods of pest control, including chemical pesticides, ineffective ( Ferry & Gomez, 2002 ; Faleiro, 2006 ; Faleiro et al, 2012 ). Recent studies showed that gut microbiota influenced the development of red palm weevil by regulating nutrient metabolism ( Habineza et al., 2019 ), and understanding the immune stimulating effect of intestinal commensal bacteria on larvae will be beneficial to the formulation of its control strategy ( Muhammad et al, 2019 ). The use of biological control methods to prevent the R. ferrugineus (mainly microbes) has achieved certain success, but the application still needs a long time ( Mazza et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The very development of the immune system is enhanced by gut bacteria ( Tables 1–4 ). Facultative bacteria aid in immune system homeostasis in fruit flies and honeybees ( Ryu et al 2008 , Kwong et al 2017 ), and in immune system priming in the red palm weevil ( Muhammad et al 2019 ). Infestations by parasitic eukaryotes are reduced by symbiont-mediated immune priming: trypanosomatids are combated in bumblebees ( Bombus ) (Latreille, Hymenoptera: Apidae) harboring core facultative symbionts ( Koch and Schmid-Hempel 2011 ), and in mosquitoes, the infection rate of the malaria parasite Plasmodium (Marchiafava and Celli, Haemospororida: Plasmodiidae) is lessened by the presence of a facultative bacterial microbiome ( Dong et al 2009 ).…”
Section: Host Defensementioning
confidence: 99%